Derivation and application of analytical model for engineering optimization of drainage well hole in coal seam roof aquifer - Zhenfang ZHOU (Meikuang Anquan)
It is an effective means to eliminate the threat of roof water damage to carry out water exploration and drainage project before coal seam mining. Selecting the typical working face of Yan’an Formation 2# coal seam as the research object, which is widely distributed in Yuanyanghu Mining Area of Ningdong Coal Field, based on the “point-source & line-sink” theory of groundwater dynamics, through the generalization of roof water drainage problem and theoretical model derivation, the analytical formula for calculating stable well flow of single inclined borehole water drainage in sandstone aquifer of coal seam roof is established. Based on the principle of “mapping well” for groundwater, analytical model of well flow for calculating the depth reduction at any point during the drainage process of bounded aquifers at the top and bottom has been derived, then, based on the principle of underground water radiation well flow, a method for optimizing the number of branch boreholes in the “radiation well” for drainage water has been proposed. By integrating the principle of “interference well” well flow superposition calculation and the formula for calculating the stable flow of incomplete wells in a finite thickness aquifer, an analytical formula for calculating the depth reduction at any point in space under the influence of the water release effect of the “well group” superposition is further derived. By constructing an optimization calculation analytical model for the spacing between drilling sites and conducting trial calculations for the spacing between drilling sites under different mining width conditions, the mathematical relationship between the spacing between drainage drilling sites and the mining width of the working face in the study area is determined. A comprehensive optimization method for drainage well hole engineering is proposed, which is applied to a typical case working face in Yuanyanghu Mining Area of Ningdong Coal Field. The drainage section of the working face roof, the spacing between drainage drilling sites, and the construction parameters of drainage drilling holes are optimized and determined. The application results show that the quantity and timeliness of water discharge are optimized to a greater extent than the traditional pre-mining roof water discharge mode through the comprehensive effect test of water control in working face mining.